Multistability in a New Chaotic System with Biscuit-Shaped Equilibrium, its Analysis, Synchronization and Circuit Design - Sambas, Aceng; Vaidyanathan, Sundarapandian; Sukono,; Zhang, Sen; Hidayat, Yuyun (Discontinuity, Nonlinearity, and Complexity, 2026)
A new 3-D chaotic system with a biscuit-like closed curve equilibrium is proposed in this paper. We analyze the qualitative properties of the new chaotic system in terms of phase plots, Lyapunov exponents, Kaplan-Yorke dimension, dissipativity, etc. We also establish that the new chaotic system has multistability with coexisting attractors. As a control application, we use integral sliding mode control for self-synchronization of the new chaotic system taken as master-slave systems. Finally, an electronic circuit realization of the new chaotic system is developed in MultiSIM, which confirms the feasibility of the system.